2023
DOI: 10.2147/copd.s425172
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Association Between Periodontitis and COPD

Kaixin Xiong,
Peng Yang,
Yujia Cui
et al.

Abstract: Periodontitis is a common chronic bacteria-initiated inflammatory disease that is closely associated with various systemic diseases, including chronic obstructive pulmonary disease (COPD). Periodontitis and COPD share similar risk factors, pathology and microorganisms. Epidemiological and clinical research have shown positive correlation between the two diseases. Individuals with severe periodontitis had a higher risk of developing COPD. Moreover, the relative risk of COPD in severe periodontitis was much high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…As a part of general health, oral health is also projected to be affected by exposure to air pollution. Environ-mental pollutants such as PM and air pollution increase the risk of periodontal and respiratory disease, causing chronic inflammation and damage to respiratory and oral tissues 14,23) . The results of previous studies suggest the possible association between PM exposure and periodontitis occurence 12,13,24) .…”
Section: Interpretation and Comparison With Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a part of general health, oral health is also projected to be affected by exposure to air pollution. Environ-mental pollutants such as PM and air pollution increase the risk of periodontal and respiratory disease, causing chronic inflammation and damage to respiratory and oral tissues 14,23) . The results of previous studies suggest the possible association between PM exposure and periodontitis occurence 12,13,24) .…”
Section: Interpretation and Comparison With Previous Studiesmentioning
confidence: 99%
“…While most of the research has been concentrated on respiratory and cardiovascular effects, there is growing evidence suggesting that PM may also have implications for oral health [11][12][13] . Studies have indicated that PM exposure can exacerbate respiratory disease, indirectly impacting oral health due to the interconnected nature of respiratory and oral systems 14) . Moreover, the potential risk of air pollution becoming a modifiable risk factor for periodontal disease has also been observed in Asian countries 12,13) .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to removing oral local promoting factors, systemic promoting factors cannot be ignored ( Kwon et al, 2021 ). Furthermore, periodontitis has been found to have negative implications on various non-communicable chronic diseases, such as benign prostatic hyperplasia (BPH) ( Wu et al, 2019 ), metabolic syndrome ( Aizenbud et al, 2023 ), and chronic obstructive pulmonary disease ( Xiong et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%